231k views
4 votes
If N and M are normal subgroups of G, and MN = mn, prove that MN is also a normal subgroup of G.

User Jeff Sharp
by
6.5k points

1 Answer

6 votes

Proof and Explanation:

  • Here, consider the product of 2 elements 'MN' as
    n_(1) m_(1) and
    n_(2)m_(2) where
    n_(1) and n_(2) ∈ N and
    m_(1) and m_(2) ∈ M

The product is given as:


(n_(1)m_(1))(n_(1)m_(1)) = n_(1)(n_(2)m_(1))m_(2)

  • Now, we know that


m_(1) ∈ G and
n_(2) ∈ N wher N ≤ G

and
m_(1)n_(2)m_(1)^(-1) = n_(3) n_(2)m_(1) = m_(1)n_(3)


(n_(1)m_(1))(n_(1)m_(1)) = n_(1)(n_(2)m_(1))m_(2) = n_(1)m_(2)n_(2)m_(1)

  • Now, we know that


n_(3) and n_(1) ∈ N and
m_(1) and m_(2) ∈ M

The product is in NM, under multiplication NM is closed

Now, we will consider the inverse of element of an element of NM as


(nm)^(-1) = n^(-1)m^(-1)

Using normality to note


(n)_(1) = n^(-1) m m^(-1) ∈ N


(nm)^(-1) = n^(1)m^(-1)

under inversion NM is closed

  • Now, to show NM is normal in G, for any g ∈ G, mn ∈ MN

and also gmn
g^(-1) ∈ MN

so, gmn
g_(-1) = (gm
g_(-1))(gn
g_(-1))

Here, first term belongs to M and the second term to N

⇒ gmn
g_(-1) ∈ MN

Hence proved that MN is a normal sub group of 'G'

User John Deer
by
6.3k points